Nanoemulsion Formulation of Palm Oil Esters for Tropical Delivery of Ibuprofen - Abdullah, Ummi Hani (2010)
Ibuprofen has been widely used for the treatment of rheumatoid arthritis and related diseases but oral consumption of this drug could cause adverse side effects. Since ibuprofen is usually given to patients over an extended period, efforts to reduce its side effect have been attempted. One promising method is topical delivery via the skin. The purpose of this study was to investigate the ability of palm oil esters nanoemulsions to deliver ibuprofen topically. Five ternary phase diagrams were constructed to find the existence of the isotropic region. The ternary phase diagram were POEs/T80:S20 (100:0)/Water, POEs/T80:S20 (90:10)/Water, POEs/T80:S20 (80:20)/Water, POEs/T80:S20 (70:30)/Water and POEs/T80:S20 (60:40)/Water. After analyzing the ternary phase diagrams, various nanoemulsions were prepared from the isotropic region in the phase diagram of POES/ T80:S20 (90:10)/Water due to the largest isotropic region exhibited. Three formulations of nanoemulsions without the addition of ibuprofen (Formulations A, B and C) and another three with the addition of ibuprofen (Formulation A’, B’ and C’) were prepared. However, these formulations have very low viscosity and have watery feel and appearance. Therefore modification with hydrocolloids; xanthan gum and carbomer 940 was done to Formulation A’. Formulation A’ was chosen to undergo modification with xanthan gum and carbomer 940 due to the highest percentage of ibuprofen released (97.50%) at 8 h as well as the formulation was with the lowest surfactant content. Xanthan gum and carbomer 940 were added from 0.2% until 1.0% to Formulation A’. Addition of xanthan gum and carbormer 940 increased the viscosity of the Formulation A’ and exhibited pseudoplastic behavior which is preferable in topical applications. The permeation profiles of ibuprofen were determined using In vitro Franz diffusion cells and were analyzed by High Performance Liquid Chromatography. Among all formulations with xanthan gum and carbomer 940, Formulation A’ Xg 0.2% (0.2% xanthan gum) showed the highest percentage of ibuprofen released (83.6%) at 8 h.